The ILO Convention No. 190 concerning the elimination of violence and harassment at work: Reasons for ratification - Dragićević Marija; Obradović Goran (Zbornik Radova Pravnog Fakulteta u Nišu)
Although the issue of violence and harassment at work has been mentioned many times in the regulations of the International Labor Organization (ILO), this issue has not been the immediate and main topic of any convention of this important international organization until recently. In that regard, the ILO Violence and Harassment Convention No. 190 (2019) is extremely important because it is the first and only international legal instrument that directly addresses violence and harassment at work. In addition, this Convention has an extremely wide scope in terms of persons and areas to which it applies. Its aim is to provide protection to employees and other persons against violence and harassment at work in all sectors, either private or public, in the formal or informal economy, in urban or rural areas. In this paper, the authors discuss the ILO Convention No. 190, its basic characteristics and definitions, its scope of application, and the actual regulation of procedure for prevention and protection against violence and harassment at work. Focusing on the existing level of legal protection of employees and other workers against violence and harassment at work in the Republic of Serbia, the authors assess whether such an act is necessary for our country, and if so, what kind of novelties and improvements it would bring to our legal system and the protection of workers when compared to the current situation.